Portuguese version of the Partner Support for Father Involvement Scale: Preliminary Validation - Antunes, Natália (2019)
Objectives Partner support in the performance of the parenting role is critical, as it increases father involvement in the care of the child. However, the measures to assess this type of support are scarce. This study presents the preliminary validation of the Portuguese version of the Partner Support for Father Involvement (PSFI) scale (confirmatory factor analysis, measurement invariance models, reliability, and concurrent and discriminant validity). Methods The participants were 486 independent (unrelated) parents, 243 fathers (Mage = 42.13, SD = 5.57) and 243 mothers (Mage = 39.67, SD = 4.78), who completed the PSFI (translated version), the EMBU and the Co-parenting Questionnaire. Results Confirmatory factor analyses showed that the Portuguese PSFI had a three factor structure, in line with the original version of the scale (χ2 = 208.690, p < .001, CFI = .949, TLI = .931, SRMR = .040, RMSEA = .083, 90% CI [.072, .095]). An invariance analysis across mothers and fathers revealed the same structure for both. Cronbach’s alpha reliabilities were acceptable. Additionally, preliminary evidence of the scale’s concurrent and discriminant validity was found. Conclusions The results point to the suitability of the measure for the Portuguese population, namely in research contexts examining one partner’s perspective of the other partner’s involvement in parenting, and to its potential applicability for cross-cultural research. The measure will also be useful in clinical settings, namely as a tool in pre and post-intervention assessment, however further studies are needed to test this type of applicability.